XÁC ĐỊNH HƯỚNG NGHIÊNG CỦA MỘT SỐ ĐỨT GÃY CHÍNH LÃNH THỔ MIỀN BẮC VIỆT NAM BẰNG PHƯƠNG PHÁP TÍNH CỰC ĐẠI GRADIENT NGANG TRỌNG LỰC - Phòng, Lại Hợp; Toàn, Đinh Văn; Vũ, Trần Anh (Vietnam Journal of Earth Sciences, 2012)
Fault incline determination of main active faults in the territory of north Vietnam by maximum horizontal gradient calculation of gravity anomaliesFault inclination is important parameter in affecting of active faulting role to geological hazards. Better understandingthis parameter is contributed to more reliable assessment of geological hazard as well as prediction and mitigation. Thispaper deals with fault inclination determined by the calculation of maximum horizontal gravity gradients. The shifting direction of the maximum gradient line derived from the higher upward continued gravity anomalies compared with the lower upward continued one is accepted as the fault inclination. Since that, the determination of the dip direction of the tectonic faults was carried out by overlaping the different schemes of maximum gradient calculated for the gravityanomalies upward continued to the different height levels. In the determination of dip direction of the fault in northern Vietnam, the calculations of maximum gradient were carried out for the gravity anomalies upward continued to the levels: Z=2.5, 5, 8, 10, 15 and 20km. The results allow us to define the incline direction of the most main active faults as: Song Hong, Song Chay, Song Lo and Dien Bien - Lai Chau, Song Ma, Son La - Bim Son and Cao Bang - Tien Yen faults.